Структура та призначення «Неолексикона Олеся Гончара» - Сніжко, Н. (Лексикографічний бюлетень, 2017)
The article is devoted to the problems of systematic lexicographic processing of the many thousands of lexical items of the outstanding Ukrainian writer-humanist, public figure academician O.T. Honchar. In the interpreted neo-lexicon the vocabulary of the three-volume edition of «Diaries» by Oles Honchar is presented, among which we distinguish thematic blocks: new names of persons; a new Ukrainian worldview; the peaks of Ukrainian spirituality; new figurative expressions; new comparative directions; new terminological combinations of words; phraseological units; epithets; periphrasis and others. We pay attention to the expressive word-formation and axiological peculiarities of the idiostyle Oles Honchar’s, among which there is a strong development of the basic formulation of words, the creation of new adjectives and adverbs of the highest and the highest degrees of comparison, the formation of a new system of evaluative means of language and the establishment of the category of spiritual values of the Ukrainian people. The dictionary is intended for macro-scientific studies of the development of language and society, the modeling of author’s and general-world paintings of the world, the study of the writer idiolect and the discernment of the great contribution of Oles Honchar to the development of the global worldview and the establishment of the Ukrainian language in the multicultural world space.